Surveillance Focus; Causes of mortality in feral wild boar in the Forest of Dean. (3rd June 2022) - Man, Cat; Williamson, Susanna
Abstract : This focus article has been prepared by Cat Man, veterinary lead of the APHA Wildlife Expert Group, and Susanna Williamson, veterinary lead of the APHA Pig Expert Group.